Big Five personality dimensions in ultramarathon runners: findings of the Ultrarunners Longitudinal TRAcking (ULTRA) Study - Jastifer, James; Hoffman, Martin (Quality in Sport, 2025)
The psychological aspect of ultrarunning is of interest in sports medicine. Ultrarunners are described as mentally tough, and have been shown in studies to be goal oriented, and intrinsically motivated. It is unknown how the personality traits of this group compare to the general population. 734 ultramarathon runners participated in this large longitudinal study. Ultramarathon runners scored significantly lower in extroversion (3.74 vs 4.44, p<.0001), and agreeableness (5.10 vs 5.23, p=.0099) compared to a control population. They scored higher in conscientiousness (5.93 vs 5.4, p<.0001), and emotional stability (5.28 vs 4.83, p<.0001), while statistically similar in openness to experiences (5.33 vs 5.38, p=0.4174). The current study dimensions of relatively low agreeableness (competitive), and extroversion (able to stay within oneself), combined with relatively high conscientiousness (organized, goal-directed), and emotional stability (stable in stressful circumstance), quantify the differences between a large ultramarathon runner population and a control group.